ORDOVICIAN ORGANIC-WALLED MICROPHYTOPLANKTON (ACRITARCH) DISTRIBUTION: THE GLOBAL SCENARIO - Servais T.; Li J.; Molyneux S.; Raevskaya E. (My University, 2003)
A number of palaeobiogeographical models for Ordovician organic-walled microphytoplankton (acritarchs, prasinophytes, and related groups) have been published during the past 30 years. A modern synthesis of Ordovician acritarch palaeobiogeography, based on previously published acritarch ‘provinces’ and global distribution models, as well as new plots on recently compiled palaeogeographical maps is presented. Review of the literature and new plots indicate that a number of preliminary conclusions can be drawn. Following minor biogeographical differentiation of acritarch assemblages during the Cambrian, ‘provincialism’ started at the Cambrian–Ordovician boundary. In the late Tremadocian a warm-water assemblage, containing the genera Aryballomorpha, Athabascaella and Lua, but no diacrodians, seems to be limited to low-latitude localities such as Laurentia and North China. From the late Tremadocian and throughout most of the Arenig a peri-Gondwana acritarch assemblage with the easily recognisable taxa Arbusculidium filamentosum, Coryphidium, and Striatotheca is present on the southern margin of Gondwana, and its distribution corresponds almost exactly with that of the Calymenacean–Dalmanitacean trilobite fauna. It seems reasonable to consider the acritarchs of Baltica as belonging to a temperate-water ‘province’, which was probably not restricted to the palaeocontinent of Baltica but had a wider distribution at about the same latitude, as some of the elements recorded from Baltica also occur in South China and Argentina. The maximum separation of the continents during the Arenigian, reflected by a pronounced biogeographical differentiation of most Ordovician fossil groups, led to the development of geographically distinct acritarch assemblages. Data from the late Middle Ordovician and the Late Ordovician remain too poor to elucidate global palaeobiogeographical patterns. The biogeographical distribution of Ordovician acritarchs appears similar to that of the resting cysts of modern dinoflagellates, primarily controlled by latitude but also following the continental margins.
Keywords: acritarchs; Ordovician; palaeobiogeography; Paleozoic::Ordovician; Палеозой::Ордовикская